Effect of soil amendments on leaf pigmentation and N status in cassava (Manihot esculenta crantz) grown in crude oil contaminated soil - S.R. Osu; N.U. Ndaeyo; G.E. Udofia (Journal of Applied Sciences and Environmental Management, 2021)
Growth studies on TMS 30572, NR8082 and Local cassava cultivars grown on previously crude oil polluted soil were conducted to assess effects of oil palm bunch ash (OPBA), dried poultry manure (DPM) on Leaf pigmentation and N2 status of test crops. In addition, physical and chemical properties of soils were determined. The pH was raised from 5.62±1.50 in control soil to values that ranged between 6.97±1.23 to 9.24±1.89 in soil treated with organic amendment. The result of organic amendment ensures reduction of C: N ratio from 50:1 in control to critical threshold that ranged between 8:1 – 10:1 for improved decomposition and soil quality. SPAD measurement revealed no significance (P≤ 0.05) in readings for both treatments and control experiments. However, the interactive effect of both cassava variety and type of amendments were significant. Cultivar TMS 30572 was found to be brought to high productivity under treatment with combined OPBA + DPM and recorded highest chlorophyll content per unit area of leaf surface with Chl. a/Chl.b ratio of 2.13 and thicker leaf blade. While Leaf chlorophyll is directly associated with the efficiency and capacity of the photosynthetic apparatus and hence chlorophyll content in this study was found to be directly related to good health status of the test crops. Results revealed that quality of crude oil contaminated soil was greatly enhanced by organic amendment.